Cervical cancer: A global health crisis - Small, William; Bacon, Monica A.; Bajaj, Amishi; Chuang, Linus T.; Fisher, Brandon J.; Harkenrider, Matthew M.; Jhingran, Anuja; Kitchener, Henry C.; Mileshkin, Linda R.; Viswanathan, Akila N.; Gaffney, David K. (Cancer, 2017)
Cervical cancer is the fourth most common malignancy diagnosed in women worldwide. Nearly all cases of cervical cancer result from infection with the human papillomavirus, and the prevention of cervical cancer includes screening and vaccination. Primary treatment options for patients with cervical cancer may include surgery or a concurrent chemoradiotherapy regimen consisting of cisplatin‐based chemotherapy with external beam radiotherapy and brachytherapy. Cervical cancer causes more than one quarter of a million deaths per year as a result of grossly deficient treatments in many developing countries. This warrants a concerted global effort to counter the shocking loss of life and suffering that largely goes unreported. This article provides a review of the biology, prevention, and treatment of cervical cancer, and discusses the global cervical cancer crisis and efforts to improve the prevention and treatment of the disease in underdeveloped countries. Cancer 2017;123:2404–12. © 2017 American Cancer Society. Cervical cancer is a leading cause of death worldwide. In this article, the authors discuss the biology, prevention, and treatment of this disease, in addition to activist efforts aimed at improving treatment and access to care.